Presynaptic Modulation of Synaptic Transmission and Plasticity by Brain-Derived Neurotrophic Factor in the Developing Hippocampus - Gottschalk, Wolfram (J Neurosci, 1998)
In addition to the regulation of neuronal survival and differentiation, neurotrophins may play a role in synapse development and plasticity. Application of brain-derived neurotrophic factor (BDNF) promotes long-term potentiation (LTP) in CA1 synapses of neonatal hippocampus, which otherwise exhibit only short-term potentiation. This is attributable, at least in part, to an attenuation of the synaptic fatigue induced by high-frequency stimulation (HFS). However, the prevention of synaptic fatigue by BDNF could be mediated by an attenuation of synaptic vesicle depletion from presynaptic terminals and/or a reduction of the desensitization of postsynaptic receptors. Here we provide evidence supporting a presynaptic effect of BDNF. The effect of BDNF on synaptic fatigue depended on the stimulation frequency, not on the stimulus duration nor on the number of stimulation pulses. BDNF was only effective when the synapses were stimulated at frequencies >50 Hz. Treatment with BDNF also potentiated paired-pulse facilitation (PPF), a parameter reflecting changes in the properties of presynaptic terminals. This effect of BDNF was restricted only to PPF elicited with interpulse intervals ≤20 msec. Changes in the extracellular calcium concentration altered the magnitude of the BDNF effect on PPF and synaptic responses to HFS, suggesting that BDNF regulates neurotransmitter release. When the desensitization of glutamate receptors was blocked by cyclothiazide or aniracetam, the BDNF potentiation of the synaptic responses to HFS was unaltered. Taken together, these results suggest that BDNF acts presynaptically. When two pathways in the same slice were monitored simultaneously, BDNF treatment potentiated the tetanized pathway without affecting the synaptic efficacy of the untetanized pathway. The selective potentiation of high-frequency transmission by BDNF appears to contribute directly to the effect of BDNF on LTP rather than indirectly by inducing the release of additional diffusible factors. The preferential potentiation of highly active synapses by BDNF may have implications in the Hebbian mechanism of synaptic plasticity.